Design and fabrication of diffractive optical elements for micro-beam shaping - Tao, Shaohua (2008)
Diffractive optical elements (DOEs) have been being used widely in the areas such as, optical imaging and displaying, information security, data storage and processing, beam shaping, and optical tweezing, etc., because the devices are more flexible, more efficient, and more compact than the conventional refractive or reflective optical elements. Studies on DOEs have to cover design, fabrication, and applications as the three aspects are closely integrated and related. In this thesis, various micro-beam shapings using DOEs have been extensively studied.